2021
DOI: 10.2147/dddt.s306367
|View full text |Cite
|
Sign up to set email alerts
|

Canagliflozin Facilitates Reverse Cholesterol Transport Through Activation of AMPK/ABC Transporter Pathway

Abstract: Background and Purpose: Cholesterol is an essential lipid and its homeostasis is a major factor for many diseases, such as hyperlipidemia, atherosclerosis, diabetes, and obesity. Sodium-glucose cotransporter 2 (SGLT2) inhibitor canagliflozin (Cana) is a new kind of hypoglycemic agent, which decreases urinary glucose reabsorption and reduces hyperglycemia. Cana has been shown to regulate serum lipid, decrease serum triglyceride and increase serum high-density lipoprotein-cholesterol (HDL-C), and improve cardiov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Members of ECIR were using SGLT2 inhibitors for 2 years before the first case of hypertriglyceridemia was incidentally noted. Hypertriglyceridemia was not an expected side effect from the review of the response of humans to this class of drugs ( Euh et al , 2021 ; Li et al , 2021 ; Luo et al , 2021 ; Zhao et al , 2021 ; Chen et al , 2022 ; Lee et al , 2022 ). However, the human diet even with diabetes is considerably higher in simple sugar and starch (35+%) ( Gray and Threlkeld, 2019 ) than the equine on restricted metabolic syndrome diets (less than 10%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Members of ECIR were using SGLT2 inhibitors for 2 years before the first case of hypertriglyceridemia was incidentally noted. Hypertriglyceridemia was not an expected side effect from the review of the response of humans to this class of drugs ( Euh et al , 2021 ; Li et al , 2021 ; Luo et al , 2021 ; Zhao et al , 2021 ; Chen et al , 2022 ; Lee et al , 2022 ). However, the human diet even with diabetes is considerably higher in simple sugar and starch (35+%) ( Gray and Threlkeld, 2019 ) than the equine on restricted metabolic syndrome diets (less than 10%).…”
Section: Discussionmentioning
confidence: 99%
“…SGLT2 inhibitors in humans and experimental animals have not been linked to worsening of the lipid profile. In fact, improvement has been reported in fatty liver parameters as well as blood levels and liver enzymes ( Euh et al , 2021 ; Li et al , 2021 ; Luo et al , 2021 ; Zhao et al , 2021 ; Chen et al , 2022 ; Lee et al , 2022 ). When details of the index case were reported, we notified veterinarians overseeing horses on SGLT2 inhibitors and suggested adding triglycerides to pretreatment screening and posttreatment monitoring.…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, treatment of HepG2 cells with canagliflozin facilitated hepatic cholesterol efflux via activation of AMPK. In turn, AMPK activation led to increased expression of the liver X receptor (LXR) and its downstream proteins, resulting in subsequent stimulation of cholesterol reverse transport [ 91 ]. LXR activation also accelerates fecal cholesterol disposal through regulation of ATP-binding cassette (ABC) transporters ABCG5 and ABCG8 expression [ 92 ].…”
Section: Sglt-2 Inhibitors In Nafldmentioning
confidence: 99%
“…LXR activation also accelerates fecal cholesterol disposal through regulation of ATP-binding cassette (ABC) transporters ABCG5 and ABCG8 expression [ 92 ]. Canagliflozin treatment resulted in reduced expressions of ABCG5 and ABCG8 and LXR, while this effect was inhibited after treatment of cells with compound C [ 91 ]. An increased AMP/ADP ratio leads to AMPK activation.…”
Section: Sglt-2 Inhibitors In Nafldmentioning
confidence: 99%
“… 11 , 12 Another study has demonstrated that canagliflozin can regulate cholesterol metabolism and improve blood lipids. 13 Moreover, Shib et al 14 have demonstrated that canagliflozin relieves the symptoms of or even delays the onsets of NASH and HCC. However, how canagliflozin alleviates the developments of hepatic steatosis and atherosclerosis has not yet been fully understood.…”
Section: Introductionmentioning
confidence: 99%